Integration of several renewable energies for internal combustion engine substitution in a commercial sailboat. (1st June 2015) - Alfonsin, V.; Suarez, A.; Urrejola, S.; Miguez, J.; Sanchez, A.
Abstract: This paper presents the technical study of a commercial sailboat conversion, originally manufactured with an internal combustion engine (ICE), into electrical hybrid propulsion system with fuel cell and batteries. Batteries are charged with electrical energy from grid when boat remains at port. The used hydrogen is generated with the electrolysis of water using energy provided through the on-board renewable system (eolic, photovoltaic and marine generation). In order to check the viability of conversion mathematical modelling is used. Firstly, hull hydrodynamic resistance is obtained through Free!Ship software. Then, this result is implemented into a global model which is developed under Matlab/Simulink ® environment. Furthermore, renewable energy and power systems are developed as Simulink ® models and a logic controller manages them. In this study, the selection of all energy and power elements is shown. Real operation sailboat under real conditions is simulated. Finally, results obtained are compared with Spanish Navigation Normative to study a possible technical feasibility. Highlights: A conceptual design of electric sailboat with renewable energies is presented. Renewable energies (eolic, solar and hydro) are stored as hydrogen. Grid energy is stored in batteries when sailboat remains at port. The integration of several renewable energies for internal combustion engine substitution in a commercial sailboat is shown. Real operation sailboat under real conditions is simulated.